2023
DOI: 10.1111/jdv.18795
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of a dermocosmetic containing Myrtus communis extract and azelaic acid for maintenance phase of adult female acne: Results from a randomized exploratory investigator‐blinded comparative study

Abstract: Background Acne is a very common condition. Currently, there are relatively few studies available to help guidance‐based decisions for its long‐term management, especially studies with cosmetic care products. We have developed a skin care product dedicated to adult female acne. Objectives Evaluate the efficacy and tolerance of the test product containing Myrtus communis extract and azelaic acid compared with a light moisturizing cream (LCM) in adult females in the acne maintenance phase. Methods A clinical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Dermocosmetic that included an ethanolic extract of myrtle leaves has been shown to reduce C. acnes biofilm and maintain acne clearance in a greater proportion of adult females compared to a control cream (85% vs. 67%, respectively). 53 Similarly, a separate dermocosmetic based on thermal water showed a marked antibiofilm activity on both C. acnes and S. aureus. 54 In 2021, Hwang et al 55 reported that daily use of a moisturizer for 4 weeks (n = 25 women) increased bacterial diversity, considered a marker of healthy skin.…”
Section: Maintenance and Protection Of Microbiome: Cleansers And Mois...mentioning
confidence: 95%
See 1 more Smart Citation
“…Dermocosmetic that included an ethanolic extract of myrtle leaves has been shown to reduce C. acnes biofilm and maintain acne clearance in a greater proportion of adult females compared to a control cream (85% vs. 67%, respectively). 53 Similarly, a separate dermocosmetic based on thermal water showed a marked antibiofilm activity on both C. acnes and S. aureus. 54 In 2021, Hwang et al 55 reported that daily use of a moisturizer for 4 weeks (n = 25 women) increased bacterial diversity, considered a marker of healthy skin.…”
Section: Maintenance and Protection Of Microbiome: Cleansers And Mois...mentioning
confidence: 95%
“…While the studies evaluating the effects of dermocosmetics on the microbiome and barrier in acne are currently sparse, some examples are presented here. Dermocosmetic that included an ethanolic extract of myrtle leaves has been shown to reduce C. acnes biofilm and maintain acne clearance in a greater proportion of adult females compared to a control cream (85% vs. 67%, respectively) 53 . Similarly, a separate dermocosmetic based on thermal water showed a marked antibiofilm activity on both C. acnes and S. aureus 54 .…”
Section: Implications For Clinical Practicementioning
confidence: 97%
“…In a multicenter, randomized, investigator-blinded trial, the efficacy and safety of this test product in acne maintenance phase was compared versus light moisturizing cream (LCM) in 26 test and 27 control subjects, respectively. 87 The products were applied twice daily on the whole face, for a study duration of 16 weeks, with subjects evaluated every 4 weeks. The efficacy was evaluated by means of the number of acne relapses and the investigator’s global assessment (IGA).…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…According to the authors, these efficacy results after a 16-week trial period suggested a trend towards acne relapse limitation by the test product, along with a benefit in maintaining long-term remission. 87 …”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Additionally, there is a lower diversity of C. acnes in acne prone skin. The interaction between skin and gut microbiome has also been considered to influence acne development and persistence, opening perspectives toward the use of probiotic therapies to reverse the dysbiosis presented in these patients (Rocha, 2018b;Rueda, 2021;Bagatin, 2023).…”
Section: Introductionmentioning
confidence: 99%